The allure of ubiquity: brand equity and brand authenticity influenced by distribution channels - Farra, Samanta Puglia Dal; Queiroz, Mauricio Jucá; Prado, Paulo Henrique Müller; Queiroz, Renata Steffanoni Bernardes de (Revista de Administração da UFSM, 2019)
Brands, being ubiquitous, can provide different perceptions of brand equity and brand authenticity among consumers. This paper aims to identify the impact of the fit between a brand, premium positioned, placed in premium channels, in contrast with popular channels placement. A product of an identical brand may have its brand value (brand equity) altered by the fit of the channel option, i.e. a channel consistent in image and brand positioning (high fit) would impact on a higher end consumer based brand equity (CBBE). We intend to contribute to enhancing the understanding of the role of channel strategy in brand value as well as the mediating effect of brand authenticity. As a methodological proposal, a couple of experiments were conducted and it was found that the consistency between brand positioning and channel (fit) leads consumers to evaluate differently the CBBE. In addition, the study found that the fit between channel and brand has a direct effect on consumer purchase intent, the higher the fit, the greater purchase intent. Likewise, it was found that the perception of brand authenticity is affected by the fit between the channel and the brands, the higher the fit with the channel, the greater the perception of brand authenticity.